2007
DOI: 10.1111/j.1365-2761.2007.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of channel catfish, Ictalurus punctatus (Rafinesque), to Edwardsiella ictaluri challenge following copper sulphate exposure

Abstract: Channel catfish, Ictalurus punctatus (Rafinesque), with or without a preliminary 24 h exposure to 2 mg copper sulphate L(-1), were challenged with 7.5 x 10(6) colony forming units L(-1) of Edwardsiella ictaluri to determine the effect of copper sulphate on disease resistance. Catfish previously exposed to copper sulphate were significantly more resistant to the bacterial challenge than those not exposed. Catfish not exposed to copper sulphate suffered 35.5% mortality while catfish exposed to copper sulphate ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…MacFarlane, Bullock and McLaughlin (1986) reported that pre‐exposure to CuSO 4 protected against F. columnare challenge in striped bass Morone saxatilis . Griffin and Mitchell (2007) demonstrated that pre‐exposure of channel catfish to CuSO 4 afforded some protection against Edwardsiella ictaluri . Rougier, Menudier, Bosgiraud and Nicolas (1996) noted that low doses of copper, pre‐ and post‐challenge with Listeria monocytogenes were protective to zebrafish, Brachydanio rerio , while high doses of copper enhanced the challenge.…”
Section: Discussionmentioning
confidence: 99%
“…MacFarlane, Bullock and McLaughlin (1986) reported that pre‐exposure to CuSO 4 protected against F. columnare challenge in striped bass Morone saxatilis . Griffin and Mitchell (2007) demonstrated that pre‐exposure of channel catfish to CuSO 4 afforded some protection against Edwardsiella ictaluri . Rougier, Menudier, Bosgiraud and Nicolas (1996) noted that low doses of copper, pre‐ and post‐challenge with Listeria monocytogenes were protective to zebrafish, Brachydanio rerio , while high doses of copper enhanced the challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Cu is widely used in aquaculture, as an algaecide and to control outbreaks of infectious diseases in fish ponds and hatcheries [4] and this practice may strongly increase the metal concentrations into aquatic ecosystems. In this scenario, aquatic organisms may suffer from chronic exposure to Cu levels, which might be 10e50 times higher than the required concentrations [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has long been hypothesized that observed differences in disease susceptibility between species and strains are due to the differing ability of the host to prevent pathogen attachment and entry at mucosal epithelial sites [260][261][262]. Fishes literally swim in a sea of pathogens, and the importance of mucus in fish defence is now well documented.…”
Section: Fish Skin Mucosal Immunologymentioning
confidence: 99%